Is respectful care provided by community health workers associated with infant feeding practices? A cross sectional analysis from India - Diamond-Smith, Nadia; Gopalakrishnan, Lakshmi; Walker, Dilys; Fernald, Lia; Menon, Purnima; Patil, Sumeet R. (BioMed Central, 2022)
Objectives Breastfeeding and complementary feeding practices in India do not meet recommendations. Community health care workers (CHWs) are often the primary source of information for pregnant and postpartum women about Infant and Young Child Feeding (IYCF) practices. While existing research has evaluated the effectiveness of content and delivery of information through CHWs, little is known about the quality of the interpersonal communication (respectful care). We analyzed the effect of respectful interactions on recommended IYCF practices. Methods We use data from evaluation of an at-scale mHealth intervention in India that serves as a job aid to the CHWs (n = 3266 mothers of children < 12 m from 841 villages in 2 Indian states). The binary indicator variable for respectful care is constructed using a set of 7 questions related to trust, respect, friendliness during these interactions. The binary outcomes variables are exclusive breastfeeding, timely introduction of complimentary feeding, and minimum diet diversity for infants. We also explore if most of the pathway from respectful care to improved behaviors is through better recall of messages (mediation analysis). All models controlled for socio-economic-demographic characteristics and number of interactions with the CHW. Results About half of women reported positive, respectful interactions with CHWs. Interactions that are more respectful were associated with better recall of appropriate health messages. Interactions that are more respectful were associated with a greater likelihood of adopting all child-feeding behaviors except timely initiation of breastfeeding. After including recall in the model, the effect of respectful interactions alone reduced. Conclusions Respectful care from CHWs appears to be significantly associated with some behaviors around infant feeding, with the primary pathway being through better recall of messages. Focusing on improving social and soft skills of CHWs that can translate into better CHW-beneficiary interactions can pay rich dividends.